Regulation of Polycomb group genes Psc and Su(z)2 in Drosophila melanogaster. - Park, S.Y.; Schwartz, Y.B.; Kahn, T.G.; Asker, D.; Pirrotta, V. (Mechanisms of Development, 2012)
Certain Polycomb group (PcG) genes are themselves targets of PcG complexes. Two of these constitute the Drosophila Psc-Su(z)2 locus, a region whose chromatin is enriched for H3K27me3 and contains several putative Polycomb response elements (PREs) that bind PcG proteins. To understand how PcG mechanisms regulate this region, the repressive function of the PcG protein binding sites was analyzed using reporter gene constructs. We find that at least two of these are functional PREs that can silence a reporter gene in a PcG-dependent manner. One of these two can also display anti-silencing activity, dependent on the context. A PcG protein binding site near the Psc promoter behaves not as a silencer but as a down-regulation module that is actually stimulated by the Pc gene product but not by other PcG products. Deletion of one of the PREs increases the expression level of Psc and Su(z)2 by twofold at late embryonic stages. We present evidence suggesting that the Psc-Su(z)2 locus is flanked by insulator elements that may protect neighboring genes from inappropriate silencing. Deletion of one of these regions results in extension of the domain of H3K27me3 into a region containing other genes, whose expression becomes silenced in the early embryo.